Evaluation of Chronic Obstructive Pulmonary Disease (COPD) and reduced ejection fraction heart failure (HFrEF) discharge medication prescribing: Is drug therapy concordant with national guidelines associated with a reduction in 30-day readmissions?. (October 2016) - Richardson, Amy; Tolley, Elizabeth; Hartmann, Jonathan; Reedus, Jasmine; Bowlin, Brandi; Finch, Christopher; Sands, Christopher W.; Self, Timothy
Abstract: Introduction: Approximately 1 in 5 hospitalized COPD patients are readmitted within 30 days of discharge. CHF coexists in more than 20% of patients with COPD, and is associated with early readmission for COPD. Reducing 30-day hospital readmissions for COPD is of intense current interest. Methodology: A retrospective chart review was performed to identify patients discharged with COPD exacerbation and HFrEF. The primary objective was to evaluate if discharge medication prescribing following guidelines for both COPD and HFrEF correlates with reduced 30-day readmission rates. Results: The study included 281 admissions with 39.1% prescribed appropriate discharge medications for both COPD and HFrEF; 30-day readmission rate was 24.5% for these patients compared to 31.1% that were not prescribed appropriate medications (p = 0.24). Beta blockers, ACE inhibitors or ARBS, and aldosterone antagonists were under-prescribed, but this did not significantly associate with increased readmission (p = 0.51, p = 0.23 or 0.99, and p = 0.18, respectively). Those prescribed hydralazine or nitrates were more likely to readmit (both p = 0.01). Diabetes and hyperlipidemia were associated with increased readmission (p = 0.01 and 0.05). Conclusions: This study did not show a significant difference in 30-day readmission rate based on appropriate discharge medications for both COPD and HFrEF. The comorbidities diabetes and hyperlipidemia and prescription of hydralazine or nitrates were significantly associated with increased readmission rate. Larger patient populations may be needed to assess if guideline based discharge medication prescribing is associated with reduced 30-day readmissions for COPD. Highlights: COPD and HFrEF medications are under-prescribed in patients with both diseases. We propose that 30 day readmissions should decline if medications for both diseases are prescribed. ACE inhibitor or ARB plus a beta-blocker were not prescribed at discharge in half of the admissions. Diabetes may be a comorbidity associated with increased 30 day readmission.